A325 HEALTH PROFESSIONAL AND COMMUNITY PERCEPTIONS REGARDING NUTRITION GUIDELINE CONTENT FOR THE GLUTEN FREE DIET. (1st March 2018) - Liu, A; Marcon, P; Turner, J; Radmanovich, K; Mager, D R
Abstract: Background: Celiac Disease (CD) is a common autoimmune gastrointestinal disorder in children, treated through strict adherence to a gluten free diet (GFD). Gluten free (GF) foods often have high levels of simple sugars, glycemic index, glycemic load and saturated fat, and are low in important micronutrients. This can lead to an increased risk for suboptimal nutrient intake and for obesity. Current national guidelines (Canada's Food Guide to Healthy Eating) do not address the optimal GFD. Thus, a specialized GF food guide to help families make healthy gluten free food choices would be beneficial. This should target health professionals, individuals with CD and their caregivers to ensure the nutritional needs of children and youth consuming the GF diet is met. Aims: To probe health professionals (HP), CD patients and their caregivers with in regards to content development for a gluten free nutrition guide. Methods: Two internet surveys (one for HP, one for members of the community) were disseminated via the Canadian Celiac Association –Chapter's Facebook/web-pages. Survey content addressed demographic variables (province, urban/non-urban, CD diagnosis, type of HP practice) and perceptions regarding the content of a food guide (nutrition topics, menu planning, etc). Descriptive statistics and thematic analysis were used to analyze closed and open-ended questions, respectively. Results: 405 individuals responded to the surveys (246 HP and 159 families). Respondents in the HP survey were mainly registered dietitians (80%) who saw pediatric CD 1–5 times per month (82%). Family respondents were caregivers, 31–40 years old (34%), who has a child with CD (51%) from Alberta (74%). HP wanted to see information on plant-based meal plans (64%), label reading (93%) and selection of processed foods (81%). Family respondents wanted to see information on CD (95%) and restaurant menu choices (72%). Both groups wanted modules on school friendly recipes and cafeteria menu options and information on added sugars (80%) and iron (82%). Conclusions: HP and families want a resource that includes information on micronutrient deficiencies in the diet and topics such as label reading and restaurant menu selection. Funding Agencies: Canadian Celiac Association - Edmonton Chapter